Aplicación web para el modelo de gestión turística sostenible comunitaria de Chimborazo utilizando Django - Baltazar Yucailla, Cristofer Vinicio (2024)
Previous research on the Django framework represented an essential component of the project. It provided the necessary technological foundation for the development of the web application aimed at sustainable community tourism management in Chimborazo. The choice of Django as the development framework was based on its reputation for robustness and efficiency and its ability to facilitate the rapid and secure development of complex web applications. Additionally, the research involved an analysis of Django's features and advantages, which subsequently served the development of the web application. The Kanban development methodology was employed to organize and manage the development process. The developed web application stood out as a comprehensive solution thanks to the use of the Django framework, in addition to being scalable, allowing for easy adaptation to the changing needs of the community and the tourism sector. It was subjected to a rigorous performance evaluation using the JMeter tool. Metrics such as efficiency, response time, and system resource usage were analysed. The results revealed 100% efficiency, meeting the standards of the FURPS quality model. The average response time was 4600 ms, below the limit suggested by the FURPS model. Additionally, system resource usage was 25%, in line with the quality model's expectations. This confirmed the system's efficacy and optimal performance.